Strategi Sukses Produksi Berbasis Ekonomi Islam: Studi Kasus Produksi Nucless di PT. Persada Nawa Kartika Kertosono - Alfin Yuli Dianto; Bhaswarendra Guntur Hendratri; Mas'u Mas'u; Mukhamad Zakariya; Mohamad Fuad Udin (Journal on Education, 2023)
The article titled "Analysis of the Islamic Economic System in the Production of NUcless at PT. Persada Nawa Kartika Kertosono" presents a qualitative study revealing the production process of NUcless at PT. Persada Nawa Kartika based on Islamic economic principles. Employing a case study method and a descriptive approach, the research collected data through interviews, observations, and documentation from employees of the company. The findings indicate that the production of NUcless at PT. Persada Nawa Kartika adheres to Islamic economic principles, although certain aspects still require improvement. Recommendations are provided for the company to consistently apply production principles and Islamic economic values to maintain a positive image in the eyes of consumers and the general public. The implication is that the sustained implementation of Islamic economic principles can enhance the company's business reputation in the market, instill trust, and support sustainable growth.